Physical chemistry (Developing a dynamic curriculum) (Washington, D.C, 1993)
This book presents reports on efforts to modernize the undergraduate physical chemistry curriculum to make it reflect the actual practice of contemporary physical chemistry. It emphasizes abinition calculations, state-to-state collisional dynamics, atmospheric chemistry, and solid-state chemistry and its interfaces with gases and liquids. It also emphasizes moder spectroscopic techniques, including laser spectroscopy, fluorescence spectroscopy, and Fourrier transform IR and NMR spectroscopy. Other chapters of the book present experiments in polymer chemistry, electrochemistry, calorimetry, real gas behavior, and mass spectroscopy
Keywords: chemistry, physical and theoretical of - study and teaching ( higher )